2021
DOI: 10.1177/87552930211042393
|View full text |Cite
|
Sign up to set email alerts
|

Rapid earthquake loss assessment based on machine learning and representative sampling

Abstract: This article proposes a new framework for rapid earthquake loss assessment based on a machine learning damage classification model and a representative sampling algorithm. A random forest classification model predicts a damage probability distribution that, combined with an expert-defined repair cost matrix, enables the calculation of the expected repair costs for each building and, in aggregate, of direct losses in the earthquake-affected area. The proposed building representation does not include explicit in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…number of stories, age, height, and plinth area) associated with ground-motion intensity provided a relevant estimate of the damage grade with a significant level of accuracy. Similar observations have also been reported by Mangalathu et al (2020b) and Stojadinović et al (2022) in their studies using the 2014 South Napa and 2010 Kraljevo, Serbian earthquake building damage dataset, respectively. Moreover, the RFR model trained on a relatively small amount of dataset (5%–20% of the test dataset) resulted in a reasonable estimate of damage; similar observation has been reported by Stojadinović et al (2022).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…number of stories, age, height, and plinth area) associated with ground-motion intensity provided a relevant estimate of the damage grade with a significant level of accuracy. Similar observations have also been reported by Mangalathu et al (2020b) and Stojadinović et al (2022) in their studies using the 2014 South Napa and 2010 Kraljevo, Serbian earthquake building damage dataset, respectively. Moreover, the RFR model trained on a relatively small amount of dataset (5%–20% of the test dataset) resulted in a reasonable estimate of damage; similar observation has been reported by Stojadinović et al (2022).…”
Section: Discussionsupporting
confidence: 87%
“…The input ground motion used was the USGS ShakeMap intensity of the mainshock, whereas the overall quality of the NBDP database results were based on the cumulative effects of the mainshock and aftershock events, which might have affected the prediction efficacy. In addition, missing building-by-building information in the NBDP database relative to their localization and their associated site condition reduce the damage prediction efficacy of the machine learning model (Mangalathu et al, 2020b; Roeslin et al, 2020; Stojadinović et al, 2022). However, we also observed that by considering the geographic locations of buildings (ward-id in our case) slightly improved the damage prediction efficacy of the RFR model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This information will provide a guideline for making emergency plans for response to an earthquake. (4) Traditionally, the main method of obtaining post-earthquake damage information has been through field survey. Although information obtained by this method is highly credible, this method often has a heavy workload and low efficiency over a large area.…”
Section: Introductionmentioning
confidence: 99%